Determinants Of Capital Structure - Evidence From Oil And Gas Tradable Sector Index (Ogti) Of Pakistan Stock Exchange - ZAHEER, DR. RUMMANA; AHMED, SYED AQEEL; ALI, SYED RASHID; ALEEM, AFSHA (The journal of contemporary issues in business and government, 2021)
financing decisions are one of the most vital decisions for companies. the given study investigates the influence of capital structure on the stock return in the context of oil and gas segment of pakistan. analysis have been conducted on 10 oil and gas companies operating in pakistan stock exchange on the basis of market capitalization over the period of 2013 to 2018.ordinary least square, fixed effect and random effect estimation methods used in the study. this study identifies the factors size, growth, non-debt tax shields, profitability, and tangibility which are important in choosing optimum capital structure. these factors are independent variables, while financial leverage is the dependent variable. results found that non-debt tax shields and profitability have the negative relationship and size, tangibility and growth have the positive relationship with the financial leverage. however, the results for size and tangibility are not statistically significant. profitability shows the negative sign and statistically significant so it may be concluded that the profitability and financial leverage are negatively related. growth is positively related with financial leverage and it is also statistically significant so hypothesis regarding growth is accepted and concludes that there is positive relationship between growth and financial leverage of the listed oil and gas firms of pakistan and follows the pecking order hypothesis. this research study is based on the data taken from the state bank of pakistan publication balance sheet of oil and gas sector companies listed on the pakistan stock exchange.